On the inherent instability of international financial markets: Natural nonlinear interactions between stock and foreign exchange markets - Roberto Dieci; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2011)
We develop a novel financial market model in which the stock markets of two countries are linked via and with the foreign exchange market. To be precise, there are domestic and foreign speculators in each of the two stock markets which rely either on linear technical or linear fundamental trading strategies to determine their orders. Since foreign stock market speculators require foreign currency to conduct their trades, all three markets are connected. Our setup entails a natural nonlinearity which may cause persistent endogenous price dynamics. Moreover, we analytically show that market interactions can destabilize the model's fundamental steady state.
Keywords: C63; F31; G12; G14; 330; Stock prices; exchange rates; market stability; technical and fundamental analysis; nonlinear market interactions; endogenous dynamics